How to Evaluate the Coordination of Green Economy, Education Development, and Technological Innovation? Take China as Example - Junqi Wu; Kui Zhang (Discrete Dynamics in Nature and Society)
The coordination of green economy, education development, and technological innovation is of great significance for reversing the trend of ecological environmental deterioration and promoting high-quality economic development. This study first designs the indicator system of green economy, education development, and technological innovation, then uses the entropy method to calculate the comprehensive level of green economy, education development, and technological innovation of 30 provinces and cities in China, and finally uses the coupling coordination model to measure the coordination level among them. The research shows that, first, the comprehensive level of green economy, education development, and technological innovation in 30 provinces and cities in China showed a rising trend from 2005 to 2016, but there were some regional differences in their levels. Second, the coordination level of green economy, education development, and technological innovation in different regions of China was in a rising trend from 2005 to 2016, but in 2005, they were extremely uncoordinated. Also, the coordination level of green economy, education development, and technological innovation in most regions of China grew very slowly from 2005 to 2010 but showed a rapid increase from 2011 to 2016. The coordination level of green economy, education development, and technological innovation in eastern China was visibly higher than that of the central region. The coordination level of the central region was higher than that of the northeast region, and the coordination level of the northeast region was higher than that of the western region. Finally, the limitations of this paper are summarized and proposed the direction of future research.